1998
DOI: 10.1002/(sici)1097-4598(199803)21:3<407::aid-mus18>3.3.co;2-y
|View full text |Cite
|
Sign up to set email alerts
|

Agrin and acetylcholine receptor distribution following electrical stimulation

Abstract: Electrical stimulation is a therapeutic modality available for the preservation of muscle function following peripheral nerve injury. Agrin, a synaptic basal lamina protein, induces accumulation of acetylcholine receptors (AChRs) and other molecules at the neuromuscular junction. Electrical stimulation of denervated muscle does not alter agrin and AChR distribution at abandoned synaptic sites, supporting the hypothesis that the existing aggregation of synaptic molecules, which may be necessary for successful r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
3
0

Year Published

2008
2008
2011
2011

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…There is a paucity of research on how NMES affects underlying neuromuscular mechanisms. Although it has been shown that exercise changes the size and complexity of both pre‐ and post‐synaptic structures of the NMJ,27–30 little is known about the effects of electrical stimulation on NMJ morphology 31–33…”
mentioning
confidence: 99%
“…There is a paucity of research on how NMES affects underlying neuromuscular mechanisms. Although it has been shown that exercise changes the size and complexity of both pre‐ and post‐synaptic structures of the NMJ,27–30 little is known about the effects of electrical stimulation on NMJ morphology 31–33…”
mentioning
confidence: 99%
“…They are most commonly found at the very tips of the nerve terminal. Staining with antibodies to agrin revealed a lack of agrin staining at these abandoned sites 5,6 . Further, AChRs were absent at the abandoned synaptic sites.…”
mentioning
confidence: 93%
“…Staining with antibodies to agrin revealed a lack of agrin staining at these abandoned sites. 5,6 Further, AChRs were absent at the abandoned synaptic sites. This was of interest because of the fact that following denervation, agrin will stay bound to the synaptic basal lamina for months.…”
mentioning
confidence: 94%